TECHNOLOGY OF STRATEGIES AND TECHNIQUES OF PEDAGOGICAL INTERACTIONS AS A TEACHER'S PROFESSIONAL SKILL (Pedagogy of Higher and Secondary Education, 2008)
The article deals with the technology of strategies a methods of pedagogical interaction as a professional teacher’s mastery which promote the effective teaching a upbringing.